Risk Factors for Gallstone Formation in Resected Gastric Cancer Patients - Paik, Kyu-hyun (Medicine (Baltimore), 2016)
Previous studies reported increased incidence of gallstone formation after gastrectomy. However, there were few reports about factors other than surgical technique. The purpose of this study is to investigate the spectrum of risk factors of gallstone formation after gastrectomy. From June 2003 to December 2008, 1480 patients who underwent gastrectomy due to gastric cancer but had no gallstones before surgery were identified. Electronic medical records were retrospectively reviewed. Gallstones were assessed by computerized tomography or ultrasound performed as surveillance for recurrence. There were 987 men (66.7%) and the median age was 59.0 years. The median follow-up period was 47.0 months. According to the surgical technique, 754 (50.9%), 459 (31.1%), and 267 (18.0%) underwent subtotal gastrectomy with Billroth I (STG B-I) and Billroth II (STG B-II) anastomosis, and total gastrectomy (TG). Within the follow-up period, gallstone formation occurred in 106 of 1480 patients (7.2%), the only 9 patients (0.6%) experienced symptomatic cholecystitis. By multivariate Cox regression analysis, age (HR 1.02, 95% CI 1.00–1.04), male (1.65, 1.02–2.67), diabetes mellitus (2.15, 1.43–3.24), ≥4% decrease of body mass index after surgery (1.66, 1.02–2.70), STG B-II (1.63, 1.03–2.57), and TG (2.35, 1.43–3.24) compared with STG B-I were associated with gallstone formation. Common bile duct stone formation occurred in 20 of 1480 patients (1.4%) and was only associated with gallstones. After gastrectomy, there were considerable numbers of patients with newly developed gallstones; however, prophylactic cholecystectomy should not be routinely recommended. Gastrectomy (STG B-II or TG), old age, male sex, diabetes mellitus, and decreased body mass index were associated with gallstones.